2014
DOI: 10.1186/bf03353221
|View full text |Cite
|
Sign up to set email alerts
|

Middle atmosphere effects of the quasi-two-day wave determined from a General Circulation Model

Abstract: A set of numerical experiments have been conducted using the National Center for Atmospheric Research Thermosphere-Ionosphere-Mesosphere-Electrodynamics General Circulation Model (NCAR TIME-GCM) to understand the effects of the quasi-two-day wave (QTDW) on the middle atmosphere horizontal wind and temperature fields. A zonal wavenumber three perturbation with a period of 48 hours and a latitudinal structure identical to the (3, 0) Rossby-gravity mode has been included at the lower-boundary of the model. A resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
167
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(193 citation statements)
references
References 74 publications
(104 reference statements)
26
167
0
Order By: Relevance
“…Numerical simulations using linear models (Hagan et al, 1993;Salby and Callaghan, 2001) and some global circulation models (Palo et al, 1999) suggest the QTDW with S=3 to be the Rossby-gravity mode. However, the waves with S=4-5 with slower phase speeds cannot as readily propagate from the lower to upper atmospheric levels and attain significant amplitudes at MLT heights.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations using linear models (Hagan et al, 1993;Salby and Callaghan, 2001) and some global circulation models (Palo et al, 1999) suggest the QTDW with S=3 to be the Rossby-gravity mode. However, the waves with S=4-5 with slower phase speeds cannot as readily propagate from the lower to upper atmospheric levels and attain significant amplitudes at MLT heights.…”
Section: Introductionmentioning
confidence: 99%
“…They definitely demonstrate global vertical and horizontal propagation of the secondary waves from the source region (e.g. Palo et al, 1999).…”
Section: Measurements and Data Analysismentioning
confidence: 99%
“…The results of the equatorial sites of Christmas Island (2 • N) and Tirunelveli (8.7 • N), as reported by Palo and Avery (1996) and Gurubaran et al (2001), respectively, show a stronger quasi-2-day wave in winter than in summer. Pancheva et al (2004) found amplitude averages in the range ∼5-26 m/s but peak amplitudes of 40 m/s (Lima et al, 2004) and 90 m/s (Pancheva, 2006) have also been reported. The amplitude of the QTDW have been observed to be modulated at ∼8-20 days (Pancheva et al, 2004) and are also correlated to the solar cycle (Jacobi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Pancheva et al (2004) found amplitude averages in the range ∼5-26 m/s but peak amplitudes of 40 m/s (Lima et al, 2004) and 90 m/s (Pancheva, 2006) have also been reported. The amplitude of the QTDW have been observed to be modulated at ∼8-20 days (Pancheva et al, 2004) and are also correlated to the solar cycle (Jacobi et al, 1997). At low-to mid-latitudes the meridional component is slightly stronger than its zonal counterpart, whereas at high latitudes the two components are comparable (Pancheva et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation